TESTS FOR THE STRIP-SPLIT PLOT DESIGN - DÍAZ-PACHÓN, Daniel Andrés; ZIMMERMANN, Francisco J. P.; LÓPEZ, Luis Alberto (Brazilian Journal of Biometrics, 2016)
In this article we present the structure of the F tests, the variance components and the approximate degrees of freedom for each of the eight possible mixed models of the strip-split plot design. We present an example to illustrate the model and compare it to more traditional settings like a three-way factorial design and a split-split plot model.